2013
DOI: 10.3844/ajbbsp.2013.102.117
|View full text |Cite
|
Sign up to set email alerts
|

ANTIOXIDANT AND ANTIMUTAGENIC ACTIVITIES OF TAIF GRAPE (<i>VITIS VINIFERA</i>) CULTIVARS

Abstract: Extract of grape Vitis vinifera has been reported to exhibit antioxidant and antimutagenic activities and the phenolic compounds play a vital role in determining these activities. Therefore; the objective of the present study was to evaluate the antioxidant and anti-mutagenic activities as well as the phenolic composition of different grape cultivar extracts collected from Taif region. The grape cultivars namely; Italian, American, Lebanese, Taify b and Taify e were collected at maturity stage to represent Tai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Palus et al (2003) correlated cadmium concentration and genotoxicity in peripheral blood cells, showing that the incidence of micronucleus in these subjects was twice as high as the control group (not exposed to heavy metals). By comparison, Fahmi et al (2013) investigated the antimutagenic activity in bone marrow mice cells of five different grape cultivar extracts and showed that all extracts had decreased micronucleus incidence after endoxan treatment. Yalçin et al (2010) treated mice with grape seed extract (at 50 and 150 mg/kg) in doxorubicininduced genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Palus et al (2003) correlated cadmium concentration and genotoxicity in peripheral blood cells, showing that the incidence of micronucleus in these subjects was twice as high as the control group (not exposed to heavy metals). By comparison, Fahmi et al (2013) investigated the antimutagenic activity in bone marrow mice cells of five different grape cultivar extracts and showed that all extracts had decreased micronucleus incidence after endoxan treatment. Yalçin et al (2010) treated mice with grape seed extract (at 50 and 150 mg/kg) in doxorubicininduced genotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, an increasing number of human clinical trials has demonstrated that the consumption of grapes and their products, such as grape juice or wine, exerts many health-promoting effects particularly the reduced risk of cardiovascular diseases, type-2 diabetes, and other chronic complications [1]. These effects result from the fact that, grapes contain many active phenolic compounds that possess antioxidant, antimutagenic [2,3], cardioprotective, anticancer, antiaging, antimicrobial [4] and anti-inflammatory properties [4,5]. According to these properties, the most important grape polyphenols are anthocyanins, flavanols (also called flavan-3-ols), flavonols [6] and phenolic acids [7].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both TN ( P. persica L.) and ATGSE ( V. Vinifera L.) act as anti-mutagens, reproducing the effects of their respective main fruits [ 50 ]. This is likely the result of their bioactive fractions being enriched in bioactive compounds, especially polyphenols, present in higher quantities compared to full-harvest fruits [ 51 ].…”
Section: Discussionmentioning
confidence: 99%